Delineating suitable wetland areas for reconnection of habitat in southwest Illinois - Mayer, Angela (Kansas State University, 2013)
Over 90 percent of presettlement wetlands in Illinois have been destroyed or impacted, yet wetlands continue to diminish. Sizable, public stretches of Illinois wetlands are lacking. Wetlands are an environmentally and economically valuable amenity, but can also enhance the quality of life of communities of people and organisms. Conservation efforts should be made to preserve natural services wetlands provide. Southwest Illinois was the focus of the study, which encompassed the counties of Jackson, Madison, Monroe, Perry, Randolph, St. Clair, and Washington. Critical areas suitable to sustain wetlands were identified through a suitability analysis utilizing Geographic Information Systems (GIS). Factors that influenced the analysis included soils, hydrology, existing wetlands, natural areas, and infrastructure. Areas ranked most suitable were in close proximity to existing wetlands or hydrologic features, contained hydric soils, and had minimal roadway infrastructure impact. Proximity to wetland and natural areas were informed by the home ranges of endangered and threatened species of Southwest Illinois. Potential suitable wetland areas for palustrine, lacustrine, and riverine wetlands were delineated on individual maps. With suitable areas known, site visits could further verify the suitability of the areas. The state of Illinois can use the specific areas to begin to focus efforts on conservation and rehabilitation to reconnect habitat and provide natural open space for a sustainable community amenity.
Keywords: Landscape architecture; Suitability analysis; Landscape Architecture (0390)